إيجاد الحل الأمثل لتغذية الأحمال الكهربائية لقرية نائية باستخدام الخلايا الكهرضوئية - مسعود صبيح; سهام عساف (Tishreen University, 2014)
يهدف هذا البحث الى تحديد تكلفة الخلايا الشمسية كمصدر للطاقة المتجددة والمدخرات كمصدر للطاقة التقليدية وإيجاد الحل الأمثل لتغذية الأحمال الكهربائية لقرية نائية. يعد استخدام الطاقات المتجددة بشكل عام والطاقة الشمسية على وجه الخصوص لانتشارها على كامل رقعة هذا العالم توجهاً صحيحاً وقد يكون إلزامياً عند الحاجة لتغذية القرى والمواقع البعيدة عن الشبكة الكهربائية، فقد يكون من أجدى البدائل المتاحة أيضاً للأحمال الكهربائية ذات الحمل المنخفض للطاقة كالمزارع أو المساحات ذات الطابع الريفي، حيث يساهم هذا الإجراء في تحسين المستوى الاقتصادي والثقافي لهذه الأماكن. قمنا من هذا المنطلق بإجراء هذه الدراسة على قرية الرابية الواقعة إلى شرق مدينة حمص بمسافة تبلغ 50[Km] ، نفذت الدراسة الفنية بتغذية كل منزل بشكل مستقل لتفادي  مد  الشبكة  بين  المنازل  المتباعدة،  أما  المرافق  العامة  فتم  تغذيتها بمنظومة خلايا كهرضوئية واحدة، استخدمت في هذا البحث نمذجة رياضة جديدة وتم صياغتها على شكل برامج حاسوبية بلغة Visual Fortran، يمكن لهذا البرنامج  تحديد حجم النظام وإجراء مقارنه لمختلف النماذج المتاحة وتحديد النماذج الأكثر موثوقية والأقل كلفة. This paper aims to determine the cost of photovoltaic cells -being a source of renewable energy, and the batteries being a source of traditional energy- for finding a solution to supplying electrical loads to a remote village. It is a reasonable practice to use the renewable energy in general and the solar energy in particular due to being freely available worldwide. This trend can be obligatory when a need arises to supply villages and sites which are far from electrical power systems. It is also one of the available options in low energy electrical loads on farms or in rural areas. This procedure will serve to improve the cultural and economic standards of these sites. In this respect,  we conducted this study in Alrabia village located 50Ks to the east of Homs. The technical study was executed by a separate supply to each house to avoid connections between remote houses. The public utilities, however, were supplied by one photovoltaic cell system. In this study, we used a new mathematical model designed in the form of Visual Fortran computer  programs. This model can also determine the size of the system by comparing various available models for selecting the cost-effective and more reliable one.